CD44 variant, but not standard CD44 isoforms, mediate disassembly of endothelial VE‐cadherin junction on metastatic melanoma cells. Issue 24 (4th November 2014) - Zhang, Pu; Fu, Changliang; Bai, Huiyuan; Song, Erqun; Song, Yang
Abstract : Loss of endothelial adherens junctions is involved in tumor metastasis. Here, we demonstrate that, in the metastatic Lu1205 melanoma cells, expression of the CD44 variant CD44v8‐v10 induced junction disassembly and vascular endothelial (VE)‐cadherin phosphorylation at Y658 and Y731. Short interfering RNA (siRNA)‐mediated CD44 knockdown or sialic acid cleavage reversed these effects. Moreover, microspheres coated with recombinant CD44v8‐v10 promoted endothelial junction disruption. Overexpression of CD44v8‐v10 but not of standard CD44 (CD44s) promoted gap formation in the non‐metastatic WM35 melanoma cells, whereas CD44 knockdown or neuraminidase treatment dramatically diminished melanoma transendothelial migration. Endothelial cells transfected with the phosphomimetic VE‐cadherin mutant Y658E supported transmigration of CD44‐silenced Lu1205 cells. Our findings imply that CD44 variant isoform (CD44v) but not CD44s regulates endothelial junction loss, promoting melanoma extravasation. Abstract : Melanoma contact induced VE‐cadherin phosphorylation and endothelial gap formation. Lu1205 melanoma cell expresses high levels of CD44v8‐v10. CD44v8‐v10 but not CD44s facilitated Lu1205‐induced endothelial gap formation. CD44v8‐v10 overexpression enhanced the ability of WM35 to induce junction loss. CD44 knockdown suppressed VE‐cadherin disassembly‐dependent Lu1205 extravasation.